2013
DOI: 10.1017/s1368980013001225
|View full text |Cite
|
Sign up to set email alerts
|

Association of vitamin D insufficiency with adiposity and metabolic disorders in Brazilian adolescents

Abstract: Objective: The present study aimed to evaluate the frequency of deficiency/ insufficiency of vitamin D in adolescents and its relationship to overweight and metabolic disorders. Design: Cross-sectional study. Nutritional status was assessed by BMI according to WHO recommendations. Dietary intake was evaluated using a 3 d dietary record. The biochemical evaluation comprised measurements of serum lipids, lipoproteins, glucose, insulin, calcidiol (25(OH)D) and parathyroid hormone. Insulin resistance was calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
2
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 31 publications
3
39
2
8
Order By: Relevance
“…The sociodemographic variables included age, gender and skin color (self-reported) (14), if receiving social government benefits and maternal education (as indirect indicators of socioeconomic status of participants). Behavioral variables covered hours of sleep per day, daily sun exposure being higher or lower than 30 minutes (7,15), practice of physical activity while being exposed to the sun, performing physical activity or inactivity and habitual dietary intake of vitamin D.…”
Section: Data Collectingmentioning
confidence: 99%
See 1 more Smart Citation
“…The sociodemographic variables included age, gender and skin color (self-reported) (14), if receiving social government benefits and maternal education (as indirect indicators of socioeconomic status of participants). Behavioral variables covered hours of sleep per day, daily sun exposure being higher or lower than 30 minutes (7,15), practice of physical activity while being exposed to the sun, performing physical activity or inactivity and habitual dietary intake of vitamin D.…”
Section: Data Collectingmentioning
confidence: 99%
“…Only three studies in Brazil working specifically with adolescents were identified, showing a prevalence above 60% for hypovitaminosis D in adolescents in the south and southeast regions of the country (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we looked at this association across the whole spectrum of adiposity. Previous studies have generally either looked at this association among the obese only (11,13,31) , while studies that have expanded their investigation beyond the high end of the spectrum have included underweight individuals within the BMI , 25?0 kg/m 2 category or assumed that the relationship is linear (3)(4)(5)(6)30,38) . The present study has specifically looked at vitamin D status at the lower end of the BMI/BF% spectrum and has provided evidence that people within the lower end of adiposity might also have compromised vitamin D levels.…”
Section: Limitationsmentioning
confidence: 99%
“…Oliveira et al [41], avaliando adolescentes brasileiros de 15 a 17 anos, encontraram menor ingestão de vitamina D entre os indivíduos com excesso de peso quando comparados com os eutróficos. Além disso, foram observados menores níveis séricos de 25 (OH) D entre aqueles com excesso de peso, obesidade abdominal e hipercolesterolemia [41].…”
Section: Discussionunclassified
“…Além disso, foram observados menores níveis séricos de 25 (OH) D entre aqueles com excesso de peso, obesidade abdominal e hipercolesterolemia [41]. Essa relação pode ser justificada pelo depósito de 25 (OH) D nos adipócitos, diminuindo sua biodisponibilidade e desencadeando uma cascata de reações hormonais que resultam em aumento da fome e diminuição do gasto energético [42].…”
Section: Discussionunclassified